A self-adaptive service provisioning framework for 3G+ - Karlich, S. (IEEE Wireless communications)
In light of the increasing acceptance of the notion of next generation networks (NGN), which results from the convergence of the fixed and mobile telecommunications, Internet, and entertainment sectors, there is a need for the realization of next-generation service delivery platforms to allow seamless and adaptive provisioning of multimedia information and communication services to mobile users. This means that in such an NGN environment different end systems, access networks, and service platforms have to be integrated. For this highly heterogeneous communications and services environment, we propose a self-adaptive service provisioning middleware framework (ASPF), which, by interoperating with existing wireless and wireline service delivery platforms, aims to enable seamless omnipresent service provisioning to mobile users anywhere, anytime, and in any context. The ASPF is intended to "liberate" applications from space and time limitations, networks, platforms, and device dependences, minimize time-to-market constraints, and eliminate major hurdles that hinder the rapid deployment of new mobile services and applications. Key to this goal is interworking/integration with current SDPs, such as IN/CAMEL, OSA/Parlay, and the emerging IMS.